Ballistic Penetration of Small-Caliber Bullet in Double-Arrow Honeycomb Core Structures with Negative Poisson’s Ratio - LIU Yangzuo, XU Cheng, MA Wuning, REN Jie, ZHANG Zhendong (Shanghai Jiaotong Daxue xuebao)
The anti-penetration performance of a double-arrow honeycomb sandwich structure with negative Poisson’s ratio (NPR) is investigated by using finite element simulation. With the penetration of small-caliber projectiles to nine types of arrowhead NPR honeycomb sandwich structures, the ballistic characteristics are obtained. The change in attitude during projectile penetration is obtained through simulation, and the dynamics simulation model of the projectile penetration double-arrow cell element is established. The simulation results show that when the thickness of the upper and lower layers are kept constant and only the double-arrow angle of the core layer is increased, the ballistic limit of the honeycomb sandwich structure is subsequently reduced. For the same honeycomb sandwich structure, there is a nonlinear relationship between the initial velocity of the bullet and the structural kinetic energy absorption rate. In addition, there is a specific velocity range within which the honeycomb sandwich structure exhibits optimal anti-penetration performance. During the penetration process, the projectile experiences an uneven distribution in the circumferential divection, which generates an asymmetric effect, altering the force environment, and leads to an unstable trajectory in the projectile’s penetration.